Significance Assessment of Amphora coffeaeformis in Arsenic-Induced Hemato- Biochemical Alterations of African Catfish (Clarias gariepinus) - Mekkawy, Imam A.; Mahmoud, Usama M.; Moneeb, Rehab H.; Sayed, Alaa El-Din H. (Frontiers in Marine Science, 2020)
Heavy metals have different adverse impacts on different life stages of fish species with attempts to use natural antioxidants to counteract their effects. So, the present study investigated the potential protective effects of Amphora coffeaeformis extract against arsenic-induced hemato-biochemical alterations in African catfish, Clarias gariepinus. The fish exposed to sub-lethal concentrations of arsenic; 19.2 and 38.3 mg/L (1/8 and 1/4 of 96h-LC50 value, 153.17 mg/L) for 15 days. The main effect of arsenic was recorded in some blood parameters such as RBC’s count, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and white blood cells. As for biochemical parameters, the main effect of arsenic was significant for alkaline phosphatase, glucose, uric acid, creatinine, albumin, globulin, and albumin/globulin. Also, the residue of arsenic in fish muscles showed significant effects. The majority of these arsenic-induced parameters were improved with dietary supplements of the diatom A. coffeaeformis. So, Amphora extract can be used as detoxification factor on fishes induced by arsenic due to its biologically active components providing protections like antioxidant, antiviral, antibacterial, and anti-inflammatory. Besides, they have excellent contents of proteins and carbohydrates which are supposed to enhance the effect of these compounds.